2022
DOI: 10.36941/jesr-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Career Choice Among Social Work Graduates

Abstract: In recent years, career decision-making has attracted research attention, especially choosing careers among graduates. Making informed and appropriate career choices are positively related to work performance and career success. The present study investigates the factors influencing career choice among social work graduates. A sample of 417 social work graduates was recruited to complete the survey. Descriptive analysis, Pearson correlation, and multiple linear regression were used to analyze the data. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Standard measurement scales which are previously validated by researchers were used in our study with reasonable modifications to measure underlying constructs. COI having five items (Zheng et al ., 2022; Lai et al ., 2014; Moody, M. B. 2020), COC with seven items were adopted from (Zheng et al ., 2022; Lai et al ., 2014; Moody, 2020), similarly, a six-item scale for CA was drawn from (Connie et al ., 2022; Lai et al ., 2014; Moody, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard measurement scales which are previously validated by researchers were used in our study with reasonable modifications to measure underlying constructs. COI having five items (Zheng et al ., 2022; Lai et al ., 2014; Moody, M. B. 2020), COC with seven items were adopted from (Zheng et al ., 2022; Lai et al ., 2014; Moody, 2020), similarly, a six-item scale for CA was drawn from (Connie et al ., 2022; Lai et al ., 2014; Moody, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…COI having five items (Zheng et al ., 2022; Lai et al ., 2014; Moody, M. B. 2020), COC with seven items were adopted from (Zheng et al ., 2022; Lai et al ., 2014; Moody, 2020), similarly, a six-item scale for CA was drawn from (Connie et al ., 2022; Lai et al ., 2014; Moody, 2020). Finally, the CC having four items were booked from (Abbas et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study that was conducted by Ong et al (2014) in Vietnam, up to 83 percent of students who have graduated in the past are considered to have deficiencies in their soft skills, and 37 percent of students are unable to acquire work due to a lack of abilities that are required for the job. Successful career planning requires numerous decisions, the ability to define goals and then the knowledge of how to achieve them, and career decisions are typically among the most difficult you will ever face, and never more so than during your undergraduate years (Zheng et al, 2022). An investigation conducted by the Ministry of Labor, Invalids, and Social Affairs found that more than 13 percent of students who graduate from undergraduate programs each year have a need for additional skills training or re-education; nearly 40 percent of students have a need for additional workplace support; and 41 percent have a need for extended time to adjust to new workplaces (Nhan, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of this study suggested that job satisfaction was important in predicting employee actions. Zheng, Bui, Nguyen, and Tran-Chi (2022) discovered a correlation between environmental, interpersonal, institutional, external, and internal factors and career selection. Preschool education is the first level of education in the national education system.…”
Section: Introductionmentioning
confidence: 99%